TREATMENT OPTIONS FOR LOCOREGIONAL RECURRENCES OF ORAL AND OROPHARYNGEAL MUCOSAL SQUAMOUS CELL CARCINOMA - I. A. Zaderenko; A. Yu. Drobyshev; R. I. Azizyan; S. V. Aliyeva (Опухоли головы и шеи)
The study included 314 patients with recurrent squamous cell carcinoma of the oral cavity and oropharynx after radical treatment. Patients were divided into groups depending on the timing – patients with early recurrence (n = 162), and late recurrence (n = 152 ), and depending on the type of treatment of recurrent tumors: conservative treatment group (n = 56 ), surgical (n = 235) and combined treatment (n = 23) group. A comparative evaluation of the effectiveness of the treatment of these patients based on the results of treatment, survival rates, the frequency and severity of complications. The conservative therapy of recurrent tumors of the oral cavity if surgical treatment is impossible is effective, especially in cases of late recurrent tumors but only surgical or combined treatment may reach the five-year survival rate in patients with recurrent tumor, cancer of the oral cavity and oropharynx.